2020
DOI: 10.1097/01.aoa.0000693728.45575.07
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Introducing Condom-catheter Uterine Balloon Tamponade for Postpartum Hemorrhage at Secondary Level Hospitals in Uganda, Egypt, and Senegal: A Stepped Wedge, Cluster-randomized Trial

Abstract: (BJOG. 2019;126:1612–1621) The World Health Organization has recommended uterine balloon tamponade (UBT) as one intervention for postpartum hemorrhage (PPH), a leading cause of maternal mortality worldwide. This is important for low- and middle-income countries (LMICs), where uterotonics, blood products, and skilled surgical teams may not be readily available. A few studies have reviewed the use of condom-catheter UBT in LMICs, but they have demonstrated conflicting findings or lacked robust evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The experimental study by Anger et al, which used a stepped-wedge design, suggests a four-fold statistically significant increase in surgical interventions or maternal deaths associated with introducing improvised UBTs (RR 4.08, 95% CI 1.07-15.58). 20 In contrast, two nonrandomised studies showed unclear effects on the composite outcome after the inclusion of the Bakri balloon (RR 0.33, 95% CI 0.11-1.03) and Bakri/Ebb balloon (RR 0.95, 95% CI 0.32-2.81). 21,23 Three studies reported hysterectomy rates and were graded as low-certainty evidence.…”
Section: Effect Of the Interventionsmentioning
confidence: 97%
See 4 more Smart Citations
“…The experimental study by Anger et al, which used a stepped-wedge design, suggests a four-fold statistically significant increase in surgical interventions or maternal deaths associated with introducing improvised UBTs (RR 4.08, 95% CI 1.07-15.58). 20 In contrast, two nonrandomised studies showed unclear effects on the composite outcome after the inclusion of the Bakri balloon (RR 0.33, 95% CI 0.11-1.03) and Bakri/Ebb balloon (RR 0.95, 95% CI 0.32-2.81). 21,23 Three studies reported hysterectomy rates and were graded as low-certainty evidence.…”
Section: Effect Of the Interventionsmentioning
confidence: 97%
“…21,23 Three studies reported hysterectomy rates and were graded as low-certainty evidence. The Anger et al trial used the condom-catheter device and found unclear results (RR 4.38, 95% CI 0.47-41.81), 20 as did both non-randomised studies that assessed purpose-designed UBT (RR 0.49, 95% CI 0.04-5.38 and RR 1.84, 95% CI 0.44-7.69, respectively). 21,23 Regarding the subsequent need for conservative surgical interventions (artery ligation, compressive sutures), the RCT (Anger et al) suggests a statistically significant increase in the risk of additional conservative interventions associated with improvised devices (RR 2.82, 95% CI 1.03-7.71), 20 whereas the non-randomised studies evaluating purpose-designed devices showed unclear results (RR 0.29, 95% CI 0.08-1.06 21,23 and RR 0.21, 95% CI 0.02-1.82 23 ).…”
Section: Effect Of the Interventionsmentioning
confidence: 99%
See 3 more Smart Citations